Patient Safety Culture from Mazandaran Clinical Nurses' Perspective - S Sharifi; A Izadi-tame; KH Hatamipour; N Sadeghigooghary; L Safabakhsh (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: Nurses are one the important groups in patients' recovery and safety and have an important role in the reduction of their mortality. The aim of the study was to identify nurses' perceptions of patient safety culture in Mazandaran's hospitals.   Material & Methods: It was a descriptive correlational study which has been done in a two month period in the hospitals of Tonekabon, Chaloos, and Ramsar. The sample was recruited by census (n= 456). Data was collected by Persian version of HSOPS, developed by Agency for Healthcare Research and Quality (AHRQ) that measures 12 dimensions of patient safety culture, and analysed by descriptive statistics and t- test, one way ANOVA, and Pearson correlation coefficient using SPSS-PC (v. 16).   Results: Amongst the 12 dimensions of AHRQ, the nurses assigned the highest score to "team work within units" (4/02 ± 0/98) and "Organizational learning-continuous development" (4/06± 0/75). They assigned the least score to "Staff" (2/39±1/11) and "non-punitive response to error" (2/53±0/98). Nurses (%53/7) reported 1-2 errors during the last year. There were significant negative correlations between the dimension of "team work within units", age, and years of experience (P< 0/05). Conclusion: It seems the patient safety culture requires some modifications to be able to create a safer clinical environment. It is suggested that punitive culture be replaced with non -punitive culture so that health care staff share their clinical errors.